2013
DOI: 10.1007/s11060-012-1040-z
|View full text |Cite
|
Sign up to set email alerts
|

H3.3 G34R mutations in pediatric primitive neuroectodermal tumors of central nervous system (CNS-PNET) and pediatric glioblastomas: possible diagnostic and therapeutic implications?

Abstract: Pediatric glioblastomas recently have been exon sequenced with evidence that approximately 30 % of cases harbour mutations of the histone H3.3 gene. Although studies to determinate their role in risk stratification are on-going, it remains to be determined whether H3.3 mutations could be found in other tumors such as pediatric primitive neuroectodermal tumors of the central nervous system (CNS-PNETs) and whether the presence of H3.3 mutations in glioblastomas could be used as diagnostic tool in their different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 23 publications
1
40
1
Order By: Relevance
“…Additional sequencing analyses with more patient samples revealed that these two types of mutations have distinct features. K27M mutations occur in younger patients (5–29 years), whereas G34R/V mutations appear in slightly older patients (9–42 years) [101103]. The majority of tumors associated with H3K27M mutation are restricted to midline locations such as thalamus, pons, brainstem and the spinal cord [102].…”
Section: Introductionmentioning
confidence: 99%
“…Additional sequencing analyses with more patient samples revealed that these two types of mutations have distinct features. K27M mutations occur in younger patients (5–29 years), whereas G34R/V mutations appear in slightly older patients (9–42 years) [101103]. The majority of tumors associated with H3K27M mutation are restricted to midline locations such as thalamus, pons, brainstem and the spinal cord [102].…”
Section: Introductionmentioning
confidence: 99%
“…This represents one out of 64 cases, and may reflect the known challenges of diagnosis high grade supratentorial CNS malignancies in childhood which can now be facilitated by specific antibodies such as reported here in the light of recent proposal for reclassification of CNS PNETs [10]. Interestingly, Gessi et al have recently reported G34R mutations in 4/33 CNS-PNET cases by sequencing and suggested that these could be defined tumour subtype [7], supporting the potential of our G34R antibody to detect G34R mutation in various TMA cohorts. However, once again further tissue was also not available for our CNS-PNET case to histological review or sequence.…”
Section: Discussionmentioning
confidence: 64%
“…The mutation hotspot codons at K27 and G34 of the H3.3 genes (AAG → ATG; GGG → AGG; GGG → GTG) were screened by pyrosequencing according to a previous report. 9) Pyrosequencing was performed using PyroGold reagents (QIAGEN GmbH, Hilden, Germany) on the PSQ 96MA instrument (QIAGEN GmbH), according to the manufacturer’s instructions. Control oligonucleotides (QIAGEN GmbH) were used to detect the background signal.…”
Section: Case Reportmentioning
confidence: 99%
“…2,4,5) Recently, recurrent H3F3A mutations of histone H3.3 have been identified as a frequent event in pediatric diffuse intrinsic brainstem gliomas (DIPGs) and thalamic glioblastomas (GBMs), associated with prognosis and survival. 69) However, due to its rarity, the relationship between the clinical course and molecular biological features in adult brain stem gliomas have still been poorly understood. …”
Section: Introductionmentioning
confidence: 99%